Kaizen: Engineering tools for development, evaluation, certification and continuous improvement of microsurgical abilities and procedures - Villanueva, Pablo Javier; Villanueva, Bárbara Magdalena; Sanmarco, Constanza Torres; Rodriguez, Hector Ivan; Arciénaga, Antonio; Lagier, Maria Eugenia; Cherian, Iype; Formento, Hector Ricardo (Seven Editora, 2023)
Introduction: microsurgical procedures are multi-variable situations, difficult to objectively analyse. Procedures evaluation-improvement-certification is a strong and developed science for engineers. Kaizen is a renamed methodology in this area. This study aims to use Kaizen tools and politics to design a protocol for hand-skills training at a microsurgical scenario, with continuous improvement ability and objective evaluation capabilities. Materials and methods: a step-by-step hand-skills training protocol was designed using Kaizen method and an experienced microvascular team opinion. It was performed by one surgeon, using a biological sample (placenta) as a surgical simulator. PDCA Kaizen protocol helped to define variables (time elapsed and mistake committed while performing a precise task) and a mistakes-score building to evaluate every single step of the procedure. The scenario was fully controlled to avoid bias. Results were statistically analysed. Results: twelve placentas were used to achieve the goals. Total working time was 13h47m03s. Longest attempt was the first one (1h49m05s/2mistakes). Shorter attempt was the fourth one (53m29sec/3mistakes). Average time was 1h15m11sec. After 7 attempts, learning curve achieves a plateau. After 12 attempts, no mistakes level was achieved, (57min37sec). Conclusion: Kaizen application to microsurgery results in a training programme that shows significant impact reducing time-needed and mistake-committed levels. Kaizen helped to use an experienced team expertise, identify useful variables, evaluate a complex procedure, data processing, and continuous-improvement-politic inclusion. Learning curves were precisely built, and teaching progress objectively measured. This method could also be applied to analyse and evaluate surgical procedures. DOI:https://doi.org/10.56238/medfocoexplconheci-049